The Impact of Palm Oil Price Decline on the Welfare of Palm Oil Farmers in Krueng Itam Tadu Raya Village, Nagan Raya Regency, West Aceh - Kholifah, Kholifah; Lubis, Fauzi Arif (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Human life is said to be prosperous when all economic and social needs can be fulfilled without shortage. As a community living in a fairly large area of oil palm plantations in Indonesia, the majority of Krueng Itam villagers have jobs as oil palm farmers so that the price of palm oil greatly affects their income. This study aims to determine the impact of the decline in palm oil prices on the welfare of oil palm farmers in the village of Krueng Itam Tadu Raya, Nagan Raya Regency, West Aceh. The research method used is descriptive qualitative with a sample of 10 respondents. Data collection techniques were carried out through observation, questionnaires, interviews, and documentation. The results of the study stated that the decline in palm oil prices had a negative impact on welfare. This is evidenced by the results of the questionnaire which showed that 70% of farmers felt that the decline in palm oil prices had a negative impact on welfare.